Forecasting the Translation Profession Development: Foresight Technology - Gavrilenko, Nataliya Nikolaevna; Biryukova, Yulia Nickolaevna (Journal of History Culture and Art Research, 2019)
The article describes the results of the conducted research based on the foresight technology that is widely used for long-term forecasting, representing a way of building a coherent and balanced image of the future. It was the first Foresight session that was devoted to the translator’s profession in Russia. The participants tried to predict the future trends, technologies, possibilities and risks of the translator’s profession in the future (up to 2030). The session was not limited to common forecasting: the task was not only to imagine the future of the translation profession but also to suggest the actions needed to achieve positive results, i.e., participants not only designed the future but also considered possible ways of developing and stabilizing the translator’s profession. The analysis of different foresight sessions in the field of education that were held in Russia, European Union, Great Britain, Canada, and the USA are also presented in the article.